Giant myxoid liposarcoma of the gluteal region: case report of patient caused delay of surgical treatment and review of the literature. Issue 10 (8th October 2018) - Willburger, Johanna C F; Kettelhack, Christoph; Fuchs, Bruno; Schaefer, Dirk J; Osinga, Rik
Abstract: Although adult soft tissue sarcoma is a rare disease, it needs individual treatment by an experienced, interdisciplinary team. We present an exceptional case of a 36-year-old woman suffering from a giant intermediate grade myxoid liposarcoma of the left buttock. She had been seen 4 years earlier but refused to undergo any treatment by then. Now suffering from a foul, ulcerating and superinfected tumor she agreed to surgical treatment. Despite delay, treatment could be performed according to the most up to date sarcoma guidelines which are discussed, including a brief review of the literature.